2018
DOI: 10.17230/ingciencia.14.28.3
|View full text |Cite
|
Sign up to set email alerts
|

Estimación de los parámetros de dos modelos para la dinámica del dengue y su vector en Cali, Colombia

Abstract: El dengue es una infección viral transmitida por la hembra del mosquito Aedes aegypti que se presenta en todas las regiones tropicales y subtropicales del planeta. En Cali, Colombia, a pesar de los controles que las autoridades de salud dicen estar haciendo, durante el año 2013, se reportaron más de 9.000 casos de dengue, de los cuales algunos han sido graves y otros han llegado a ser letales. Para la transmisión del virus del dengue, los modelos matemáticos que simulan la dinámica de la población infectada, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In particular, and are entomological parameters and their values are during the 2010 dengue outbreak affected by the temperature and humidity variations. [28][29][30] Parameters and related to the disease transmission may vary with the virulence of circulating DENV strains. 31,32 Finally, the average vectorial density depends on the total size of the vector population (assuming that the total number of human residents remain invariable), and its value is affected not only by the climatic changes, [28][29][30] but also by the efficiency of routinary control actions, such as periodical treatment of mosquito breeding sites with larvicides, and by inflow and outflow of daily commuters.…”
Section: Parameter Values and Initial Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, and are entomological parameters and their values are during the 2010 dengue outbreak affected by the temperature and humidity variations. [28][29][30] Parameters and related to the disease transmission may vary with the virulence of circulating DENV strains. 31,32 Finally, the average vectorial density depends on the total size of the vector population (assuming that the total number of human residents remain invariable), and its value is affected not only by the climatic changes, [28][29][30] but also by the efficiency of routinary control actions, such as periodical treatment of mosquito breeding sites with larvicides, and by inflow and outflow of daily commuters.…”
Section: Parameter Values and Initial Datamentioning
confidence: 99%
“…[28][29][30] Parameters and related to the disease transmission may vary with the virulence of circulating DENV strains. 31,32 Finally, the average vectorial density depends on the total size of the vector population (assuming that the total number of human residents remain invariable), and its value is affected not only by the climatic changes, [28][29][30] but also by the efficiency of routinary control actions, such as periodical treatment of mosquito breeding sites with larvicides, and by inflow and outflow of daily commuters. 31,33 Furthermore, it is worthwhile to note that the values of parameters ( , , , , , ) given in Table 2 bear little difference with other estimations obtained from the incidence datasets collected in Cali, Colombia during different years.…”
Section: Parameter Values and Initial Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with estimations performed in Reference [32] for average daily temperature (23.9 • C) in the city of Cali, Colombia, and other data found in scientific literature, Table 2 displays numerical values assigned to all constant parameters of the dynamical system (1) which will be kept unaltered during the computational experiments involving numerical solutions of the optimal control problem (10).…”
Section: Preliminary Settingsmentioning
confidence: 62%
“…It also holds that Q 0 < Q, which is in line with common sense. Using the values of parameters of the model (1) without predacious species (x(t) = 0, t ≥ 0, see also Table 2 ahead) estimated for the climatic conditions of the city of Cali, Colombia [32], it had been shown that Q > 1 for all temperature ranges. This explains durable persistence of the mosquito population in Cali, Colombia all the year around.…”
Section: Model Descriptionmentioning
confidence: 99%